A COMPARATIVE ANALYSIS OF SYNONYMOUS AND ANTONYMOUS EXPRESSIONS OF THE CONCEPTS “BEAUTY/UGLINESS” IN ENGLISH AND UZBEK - Tojiboyev, I.U (International Conference on Arts, Society & Humanities, 2026)
This article focuses on the analysis of lexemes representing the concept of "beauty/ugliness" in English and Uzbek languages and the analysis of synonymous and antonymic relationships between them. Synonyms are, to a certain extent, factors that indicate the level of development of a language, its richness. Correctly distinguishing between synonyms and using them correctly in their proper place allows you to clearly express your thoughts, clearly show the attitude of the subject to the object about which he is thinking. When defining synonyms, it is necessary to take into account the original meaning of the word and its meaning realized in the context, as well as its figurative meaning. Antonyms are one of the phenomena that are determined on the basis of the semantic relationship between language units. Defining antonyms, on the one hand, leads to a deeper understanding of the lexical meaning of words, and on the other hand, helps to distinguish the meanings of one word in polysemy, and is also useful in defining synonyms. The article takes a broad approach to this issue using examples.